Student Management Strategy Based on Multiculturalism Through the Academic Calendar at Miftahul Ulum Islamic Boarding School Tanjunganom Nganjuk - Umami, Isfiana Oktaria Nasihatul; Nirmala, Devi Widya (Cakrawala Journal is a scientific journal published by Nahdlatul Ulama Islamic Institute (IAINU) Kebumen. This journal focuses on the Islamic Education Management Study and Social Studies which is published twice a year.IAINU Kebumen, 2025)
This study examines the strategy of managing students at the Miftahul Ulum Islamic Boarding School using a multicultural approach, including the role of the management structure and departmental work programmes in creating an inclusive environment. The purpose of this study is to describe the managerial patterns (planning, organising, directing, and supervising) applied by the institution in managing religious learning activities and to assess how multicultural values are internalised through the academic calendar and activities at Madrasah Diniyah. Miftahul Ulum Islamic Boarding School. Currently, the Miftahul Ulum Islamic Boarding School is led by KH. Ashfiya' Hamida Mujahid and the Chair of the Foundation is Ning Arifah Millati Agustina, M.H.I. The General Chair of the Boarding School is Agus H. Nur Muhammad Syaiful Rijal, M.H.I, while the position of Secretary is held by M. Wahyu Habibullaah. while the Treasurer is held by Ning Layyinah Nur Chodijah, Lc. This structure also includes various departments, including the Education Department, Health and Hygiene Department, Security Department, and Jam'iyyah Department, which implement work programmes such as prayer/recitation attendance and muhadhoroh activities as well as tambourine training. A qualitative research method with a case study approach was used; data was collected through observation, interviews, and documentation studies, including academic calendar tables and documentation of madrasah activities. The results showed that student management at the Miftahul Ulum Islamic Boarding School had implemented a structured classical managerial cycle, integrating textbook material, Arabic, and regional languages, as well as organising religious and social activities as a means of inclusive character building and appreciation of diversity. Supporting factors include the leadership of the caretaker/head of the madrasah, support from the community/alumni, and the existence of BOSDA (Regional School Operational Assistance); while obstacles include limited facilities and infrastructure, disparities in student abilities, and the need to improve educators' capabilities in multicultural pedagogy. The practical implications of this study recommend strengthening the capacity of educators, developing SOPs for activities, and establishing a multicultural indicator evaluation system to improve the quality of management and sustainability of the program